ENHANCED GENOGRAM AND ECOMAP AS INSTRUMENTS FOR PSYCHOSOCIAL RESEARCH AND INTERVENTION - Borges Gomes, Thaísa; Dalla Vecchia, Marcelo [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2023)
Genogram and ecomap are tools developed for health care settings, focusing on family health, with broad potential for application in psychosocial research and intervention, remarkably standing out its practicality and low application costs. Despite bearing multiple possibilities of use and ease of development, they are blatantly underusedregarding health assistance and research in Brazil. Therefore, we seek to review and propose an expansion to the scope of use of these instruments, adapting them to a Brazilian historical and cultural context. This paper applied literature review as the basis for the preparation of an initial semi-structured interview script, which supported the proposal of the Enhanced Genogram and Ecomap (Genograma e EcomapaAmpliado– GEA), updating its graphic representations in accordance with the multiplicity of contemporary family arrangements. The potentiality of GEA was confirmed as a way of identification and characterization of the family history of the index-subject and his social support network.
GENOGRAMA E ECOMAPA AMPLIADO COMO INSTRUMENTOS DE PESQUISA E INTERVENÇÃO PSICOSSOCIAL
Keywords: Family; Genogram and ecomap; Psychosocial intervention; Qualitative research; Social support network